Measure and analyze the relationship between oil prices and the Iraqi dinar exchange rate - عبد خضير, ايمان; علوان, حسين حسب الله (Journal of Economics and Administrative Sciences, 2014)
In this research, we discussed and analyzed the relationship between oil prices and the U.S. dollar exchange rate in Iraq. The study adopted the descriptive analysis and econometrics analysis. The descriptive analysis refers to the rise (fall) in crude oil price lead to appreciate (depreciate) in the Iraqi dinar exchange rate, though the channel of the international reserves. The econometrics analysis is based on monthly data covered the period (December/2002 – December/2011), the unit root test, co-integration test, vector error correction model, and Granger causality test have been adopted in this research to check the existence and direction of this relationship. The results refer to the long-run relationship between oil price and Iraqi dinar, Granger causality test refer to one direction causality run from oil price to Iraq dinar exchange rate. On other hand, VECM refers to two causalities long-run relationships (i.e. both oil price and exchange rate cause each other). But the direction of the relationship from the Iraqi dinar exchange rate to the crude oil price is not accepted by the economic logic, because it is not possible the IQD affect the crude oil prices